Interdisciplinary Creativity - Aldunate Bengolea, Javiera; Lira Avilés, Matías (Base Diseño e Innovación, 2016)
In April 2015—and thanks to the agreement between Universidad del Desarrollo and the Stanford Technology and Venture Program (STVP), from Stanford University—four Chilean instructors had the opportunity to be part of the Faculty Fellow Program, an immersion program in innovation. Our goal? Perform a diagnostic of the Center for Interdisciplinary Innovation, iCubo, six years after its creation, and propose improvements to refine it and, in this way, generate a greater impact on students.